A new species of Pseudoleptochelia Lang, (Crustacea: Peracarida: Tanaidacea: Leptocheliidae) from the Northwest Atlantic with observations on the status of the genus - Morales-Núñez, A.G., Heard, R.W., & Alfaro, M. (Zootaxa, 2013)
Pseudoleptochelia juliae n. sp. is described from Puerto Rican waters in depths from 1 to 28 m. The new species and P. fairgo from western Australia are the only members of the genus as defined in this revision that have a distinct process on the posterior margin of the cheliped carpus. The male of P. juliae is distinguished from that of P. fairgo by this process being sub-acute and having a distinctly narrower propodus. Lang’s generic diagnosis for the female of Pseudoleptochelia is incorrect, which has led to confusion. Based in examination of Mediterranean specimens attributed to the type species P. anomala (Sars), Pseudoleptochelia is rediagnosed to contain seven species; P. anomala; P. fairgo; P. juliae; P. magna; P. mortenseni; P. occiporta; and P. straddi., The genus is reviewed and discussed and the taxonomic status for the remaining nine species previously assigned to the genus is re-evaluated. Pseudoleptochelia shares similarities with the more recently described Pacific genera Konarus and Parakonarus and to a lesser extent to the highly derived genus Makraleptochelia.